Comparative Sensitivity of Solid-Phase Versus PEG Enhancement Assays for Detection and Identification of Red Blood Cell Antibodies. (9th November 2022) - Abdelmonem, M; Dussaq, A; Cai, W; Tang, M; Nguyen, A; Papakonstantino, K; Cabungan, M; Yoshizuka, S; Hollenhorst, M
Abstract: Introduction/Objective: Identifying antibodies to red blood cell (RBC) antigens is one of transfusion medicine's most critical and challenging issues. There are 354 RBC antigens recognized by the International Society of Blood Transfusion. Accurate identification of clinically significant alloantibodies is imperative for identifying and preventing hemolytic transfusion reactions and hemolytic disease of the fetus and newborn. We compared the performance of the tube (polyethylene glycol–indirect antiglobulin test [PEG-IAT]) and solid-phase techniques for antibody identification. Methods/Case Report: We performed a retrospective study on all antibody screens and identifications performed between 2007–2021 at Stanford Hospital. Over this period, 631, 535 antibody screens were performed predominantly using an automated solid-phase technique. Subsequent antibody identification studies were performed using manual tube testing (PEG-IAT) and automated solid-phase techniques. Results (if a Case Study enter NA): Antibody screening resulted in 28, 316 (4.5%) positive samples with at least one antibody. Antibody identification performed on both platforms identified 50 discordant [DMH1] samples. 8 anti-Jka, 2 anti-Jkb, 1 anti-S, and 1 anti-M were detected by automatic solid-phase technique but were not detected by PEG-IAT. 20 anti-E, 6 anti-K, 2 anti-Fya, 2 anti-c, 2 anti-C, 2 anti-Fyb, 1 anti-cE[DMH2], 1 anti-e, 1 anti-M, and 1 anti-S were detected by PEG-IAT but were negative by automated solid-phase technique. Anti-E had the least sensitivity (98.99%) in the automated solid-phase technique, while anti-Jkb had the least sensitivity (98.78%) in PEG-IAT. Conclusion: This is the first robust 15-year study comparing methodologic sensitivity to detect clinically significant alloantibodies. The incidence of discordant results between the PEG-IAT and solid-phase technique was low. Among discordant samples, anti-Jka was commonly detected by solid-phase but not by PEG-IAT. In contrast, anti-E was commonly detected by PEG-IAT but not by the solid phase.